Pemberdayaan Masyarakat Dalam Rangka Meningkatkan Kesadaran Akan Kebersihan Lingkungan Melalui Bank Sampah Organik Dan Anorganik - Ani Yusmitasari; Andri Juniarta; Dewi Arifta Sari; Diky Bustomy; Nadya Jihana Putri; Nurul Rusita Sari; Prasya Tsaqof Vendra; Riyan Erwin Hidayat (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2024)
community empowerment is a strategic step in increasing awreness of thr importance of environmental cleanliness. This study aims to analyze the roleof organic and inorganic waste banks as a means of education and waste management in public places. By actively involving the community, this program not only increases awareness of good waste management, but also encourages participation in maintaining environmental cleanliness. The methods used include observation and interviews with several village officials and cadres. The expected results are changes in community behavior towards a cleaner and more environmentally friendly lifestyle. Through tihis initiative, it is hoped that a cleaner and healthier environment will be created, as well as a collective awareness of maintaining environmental sustainability.